Approaches to the Development of Drugs with the Use of Modern Statistical Software Concepts and Quality-by-Design - A. N. Golubev; T. Sh. Nguyen; A. V. Basevich; V. V. Sorokin; I. E. Kaukhova; A. L. Marchenko; E. M. Smirnova (Разработка и регистрация лекарственных средств)
Introduction. The development of the composition of drugs is very difficult and long process. To implement it, it is currently recommended to apply a modern approach – quality through the development of Quality by design. One of the methods for introducing this approach is the use of multifactorial experiments.Aim. The aim of the work was to develop the composition and technology of effervescent tablets using the Minitab program.Materials and methods. For the study used the program Minitab (ver. 18.), Minitab LLC, USA. The program created an experiment plan and evaluated those obtained on the basis of its models using regression analysis.Results and discussion. The composition and technology of effervescent tablets was developed by direct compression using the principles of Quality by design. Algorithms of actions for using the Minitab software package for development are proposed. An experiment plan was constructed and models of the dependence of quality indicators on the composition and technological parameters were generated. The resulting sub-sections were analyzed using regression analysis tools.Conclusion. Based on the results of the work, the composition of effervescent tablets obtained by direct compression technology, as well as the algorithm of drug development in the Minitab program, was proposed.